Red de innovación agrícola para productores de la parroquia San Lorenzo de Tanicuchi - Claudio Pruna, Darwin Rodrigo (2021)
Agricultural activity is a fundamental part of rural territorial development, which, although it has been transformed by globalization processes, continues to be the source of income and self-sufficiency for small producers. The strengthening of this economic activity requires the conceptualization of the development process as the combination of the economic, institutional, environmental and social dimensions. In the last two aspects, the changes adopted towards agroecological systems that preserve the environment, and the formation of networks through the consolidation of the social fabric should be considered.